Long-Term Retinal Neurovascular and Choroidal Changes After Panretinal Photocoagulation in Diabetic Retinopathy - Huang, Tian; Li, Xiaoli; Xie, Jie; Zhang, Liang; Zhang, Guanrong; Zhang, Aiping; Chen, Xiangting; Cui, Ying; Meng, Qianli (Frontiers in Medicine, 2021)
Purpose: To evaluate the long-term retinal microvascular, neural and choroidal changes in patients with severe non-proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) following panretinal photocoagulation (PRP). Methods: Forty-five eyes of 28 patients with treatment-naive severe NPDR and PDR were included and followed for 12 months after PRP. Microvascular and neural changes in macular and peripapillary area were assessed using optical coherence tomography angiography. Subfoveal choroidal thickness (SFCT) was measured using optical coherence tomography. Linear mixed-effects model was used to highlight differences for variables after adjusting for sex, age and axial length. Results: Compared to baseline, there were no statistical differences in best-corrected visual acuity (BCVA), macular and peripapillary vessel density (VD) and SFCT following PRP. Macular thickness significantly increased at 1 and 3-6 months after PRP (all P < 0.05), while peripapillary retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thickness significantly increased at 1 month postoperatively (all P < 0.01). Global loss volume and focal loss volume significantly decreased at the same timepoint (all P < 0.05). Conclusion: The unchanged BCVA, VD, thickness of RNFL and GCC and SFCT during the 12-month follow-up period suggest that PRP may prevent the retinal neurovascular and choroidal damage.